Review of design solutions for nominally strip (continuous) foundations (Academic journal Industrial Machine Building Civil Engineering, 2018)
The paper reviews the existing designs of nominally strip (continuous) foundations that are offered in foundation engineering, that due to their shape (configuration) of contact with the base enable more rationally to design foundations for continuous structures of buildings and facilities. The advantages and disadvantages of continuous  foundations different types are shown, and some calculation methods and methodologies when calculating these foundations in interaction with soil bases are given.
Keywords: tapered pile; soil subsidence; lateral surface; additional load friction forces